The multiple products, functions and users of natural resource systems - Swallow, B.M. (International Food Policy Research Institute, 1997)
This paper presents an analytical framework for guiding studies of the use and management of natural resource systems in which: (i) several goods and services of value are produced; (ii) resource users have multiple objectives vis-a-vis collective management of the natural resource system; and (iii) sub-groups of resource users are distinguished by their property rights, endowments and preferences. The framework is motivated and validated by reference to rangeland systems in Africa. Several implications for research and policy emerge.